Glaucoma - Jonas, Jost B.; Panda-Jonas, Songhomitra (The lancet, 2017)
Summary: Glaucoma is a heterogeneous group of diseases characterised by cupping of the optic nerve head and visual-field damage. It is the most frequent cause of irreversible blindness worldwide. Progression usually stops if the intraocular pressure is lowered by 30-50% from baseline. Its worldwide age-standardised prevalence in the population aged 40 years or older is about 3·5%. Chronic forms of glaucoma are painless and symptomatic visual-field defects occur late. Early detection by ophthalmological examination is mandatory. Risk factors for primary open-angle glaucoma—the most common form of glaucoma—include older age, elevated intraocular pressure, sub-Saharan African ethnic origin, positive family history, and high myopia. Older age, hyperopia, and east Asian ethnic origin are the main risk factors for primary angle-closure glaucoma. Glaucoma is diagnosed using ophthalmoscopy, tonometry, and perimetry. Treatment to lower intraocular pressure is based on topical drugs, laser therapy, and surgical intervention if other therapeutic modalities fail to prevent progression.